2008
DOI: 10.1093/jn/138.5.921
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Transgenic Goats’ Milk Influences Gastrointestinal Morphology in Young Pigs ,

Abstract: Transgenesis provides a method of expressing novel proteins in milk to increase the functional benefits of milk consumption. Transgenic goats expressing human lysozyme (hLZ) at 67% of the concentration in human breast milk were produced, thereby enhancing the antimicrobial properties of goats' milk. The objective of this study was to investigate the impact of pasteurized milk containing hLZ on growth, the intestinal epithelium, and an enteropathogenic Escherichia coli (EPEC) infection in young weaned pigs. Pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
97
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 39 publications
10
97
1
1
Order By: Relevance
“…Because orally administered lysozyme must interact with the gastrointestinal tract and be absorbed to fully exert an effect, we used a dose based more on pharmacological effects than on naturally occurring physiological concentrations. Specifically, the dose we used was equal to the higher of two concentrations determined to be non-toxic in rats (Cerven et al, 2008), in line with the highest level provided to growing chicks (Humphrey et al, 2002), and approximately an order of magnitude higher than the dose provided to growing pigs (Brundige et al, 2008). …”
Section: Additional Details About Lysozyme Supplementationmentioning
confidence: 99%
See 3 more Smart Citations
“…Because orally administered lysozyme must interact with the gastrointestinal tract and be absorbed to fully exert an effect, we used a dose based more on pharmacological effects than on naturally occurring physiological concentrations. Specifically, the dose we used was equal to the higher of two concentrations determined to be non-toxic in rats (Cerven et al, 2008), in line with the highest level provided to growing chicks (Humphrey et al, 2002), and approximately an order of magnitude higher than the dose provided to growing pigs (Brundige et al, 2008). …”
Section: Additional Details About Lysozyme Supplementationmentioning
confidence: 99%
“…Rather, lysozyme-supplemented pigeons exhibited stronger inflammatory responses to LPS with greater increases in oxidative damage and oxygen consumption. Previous studies suggest that preventative and therapeutic administration of lysozyme has net positive effects in terms of growth and health (Sava, 1996;Humphrey et al, 2002;Brundige et al, 2008). In young pigs, consumption of lysozyme-supplemented milk improves gastrointestinal health and protects against bacterial infections without limiting growth (Brundige et al, 2008).…”
Section: Lysozyme Supplementation Lps Challenge and Their Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have developed transgenic dairy goats that express human lysozyme (HLZ) in their milk at 68% the level normally found in human milk (29) with the goal of incorporating the beneficial protective properties of human milk into readily available livestock milk in order to promote the intestinal and overall health of people of all ages. We previously demonstrated that consumption of milk from HLZ-transgenic goats by animal models results in the modulation of Escherichia coli and total coliform levels in the small intestine as determined using standard culture techniques (30), resistance to intestinal colonization by pathogenic E. coli (5), and histological and cytokine changes coupled with increases in serum metabolite makers indicative of improved gastrointestinal (GI) health (6,10).…”
mentioning
confidence: 99%